2013
DOI: 10.1128/aac.02370-12
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Luliconazole Solution 10-Percent in Patients with Moderate to Severe Distal Subungual Onychomycosis

Abstract: The study objective was to evaluate the safety, tolerability, systemic exposure, and pharmacokinetics (PK) of 10% luliconazole solution (luliconazole) when topically applied once daily to all 10 toenails and periungual areas in patients with moderate to severe distal subungual onychomycosis. In this single-center, open-label study, 24 patients applied 20 mg/ml of luliconazole (twice the clinical dose) for 29 days with a 7-day follow-up. Complete PK profiles were determined on days 1, 8, 15, and 29. Safety/tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…5,17,28,29 Skin irritation indices have been reported to be within the range specified for a safe product. 5 No toxicity issues have been reported in guinea pig model studies of tinea pedis induced with T. mentagrophytes.…”
Section: Safety and Tolerabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…5,17,28,29 Skin irritation indices have been reported to be within the range specified for a safe product. 5 No toxicity issues have been reported in guinea pig model studies of tinea pedis induced with T. mentagrophytes.…”
Section: Safety and Tolerabilitymentioning
confidence: 96%
“…17 In this study, luliconazole showed very low systemic absorption and excellent local tolerability with no evidence of laboratory abnormalities or subject discontinuation, 33 with plasma concentrations near or below the lower limit of quantification (0.05 ng ml À1 ). 17 In contrast, median nail concentration of luliconazole 7 days after the last application was 35 mg g À1 ; 17 thousands of times greater than the MIC90 of T. rubrum and T. mentagrophytes (0.001 lg ml À1 ). 4 Very low levels of luliconazole were measurable in plasma up to 7 days after the last application, indicating that the nail plate may serve as a reservoir allowing its slow release into the nail bed.…”
Section: Clinical Experience In Onychomycosismentioning
confidence: 97%
“…Luliconazole is a novel imidazole currently under development. Pharmacokinetic and safety results from phase 1 studies in patients with onychomycosis have demonstrated high concentrations of luliconazole within the nail plates of the great toe and have shown that this agent is well tolerated when administered as a 10% solution (7). In vitro studies with a limited number of isolates have also reported potent activity of this agent against dermatophytes and other causative agents of dermatophytosis, including onychomycosis (8)(9)(10).…”
mentioning
confidence: 99%
“…Other formulations with terbinafi ne that are undergoing phase II trials include MOB-015 and TMI-358. Luliconazole has completed phase I and IIa testing for treatment of moderate to severe distal subungual onychomycosis with positive results (Jones and Tavakkol 2013 ). Refer to Table 21.1 for a comprehensive list of new topical antifungal treatment options for onychomycosis.…”
Section: Topical Treatmentmentioning
confidence: 99%